2019
DOI: 10.1016/j.dib.2019.104073
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on the effect of hardwood biochar on soil gravimetric moisture content and nitrate dynamics at different soil depths with FTIR analysis of fresh and aged biochar

Abstract: The goal of this research work was to determine widespread impact kiln-produced hardwood biochar has upon temperate agricultural soil characteristics in a long-term field experiment. This dataset is supplementary to the submitted research by [1] and presents select physical and chemical characteristics of the biochar and field plots amended with hardwood biochar. Data on soil gravimetric moisture content (GMC), soil acidity and soil nitrate-N concentration at lower depth of soil under different biochar applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The maximum tensile strength of ca.43 MPa was observed at a biochar concentration of 10%, while the tensile strength decreased by 41% when the concentration was increased to 15%. Similar to the current study, Richard et al observed a decrease in tensile strength with increasing biochar concentration when rice husk biochar was introduced into the polyester matrix 24 . In comparison to the neat vinyl ester, the biochar‐added composite has a very high axial strength.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The maximum tensile strength of ca.43 MPa was observed at a biochar concentration of 10%, while the tensile strength decreased by 41% when the concentration was increased to 15%. Similar to the current study, Richard et al observed a decrease in tensile strength with increasing biochar concentration when rice husk biochar was introduced into the polyester matrix 24 . In comparison to the neat vinyl ester, the biochar‐added composite has a very high axial strength.…”
Section: Resultssupporting
confidence: 85%
“…Similar to the current study, Richard et al observed a decrease in tensile strength with increasing biochar concentration when rice husk biochar was introduced into the polyester matrix. 24 In comparison to the neat vinyl ester, the biochar-added composite has a very high axial strength. The bonding between polymers and biochar improved the performance significantly.…”
Section: Mechanical Properties Of the Polyester-biochar Micro-particl...mentioning
confidence: 99%
“…Fourier transform infrared spectroscopy analysis: The infrared spectrum analysis results of SRBC500 prepared at different pyrolysis times are shown in Figure 3. Fourier transform infrared spectroscopy (FTIR) is one of the effective means to measure the functional groups in biochar (Cole et al 2019). Pyrolysis time has an important influence on the structure and properties of biochar, which is mainly due to the different carbonization degrees of Spirulina residue, thus changing the functional groups on the surface of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…The bands around 1,490 cm −1 represented the stretching vibration of aromatic CO and benzene ring CC, and the band at 750 cm −1 was assigned to the bending vibration of CH and OH. [ 43 ] The absorption peaks at 1,100–900 and 553 cm −1 were ascribed to the FeO stretch vibration. [ 3,38 ] These characteristic peaks can be clearly observed on BC‐nPd/Fe, indicating that nPd/Fe was successfully loaded on the BC.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] BC has a porous structure and possesses a large surface area rich in diverse functional groups. [ 42,43 ] BC can be successfully used to disperse and stabilize nanoparticles, thereby enhancing their performance in environmental applications. [ 39 ] Wang et al [ 42 ] reviewed the preparation of BC from different raw materials and its capacity to remove various contaminants after loading nZVI.…”
Section: Introductionmentioning
confidence: 99%